Application of the holistic methods in analysis of organic milk - Anka Popović-Vranješ; Radovan Pejanović; David Cvetanović; Marija Jevtić; Milka Popović; Danica Glavaš-Trbić; Goran Jež (Mljekarstvo)
Organic farming has advantages in terms of environmental protection, biodiversity, soil quality, animal welfare and pesticide residues. Unlike conventional production “organic chain” means that healthy soil leads to healthy animal feed, leading to healthy cows with normal milk, which eventually leads to healthy consumers. Since this must be scientifically proven, there is an increasing need for scientific methods that will reveal the benefits of organic food. For this purpose holistic methods such as biocrystallization and methods of rising picture are introduced. Biocrystallization shows that organic milk is systematically more “balanced” and that there is more “ordered structure” and better “integration and coordination.” Previous studies using biocrystallization method were performed on the raw milk produced in different conditions, differently treated milk (heat treatment and homogenization) and on butter. Pictures of biocrystallization are firstly visually assessed and then by the computer analysis of texture images, which are used to estimate the density of images. Rising picture method which normally works in parallel with biocrystallization can differentiate samples of Demeter, and organic milk from conventional production and milk treated differently during processing. Organic milk in relation to conventional shows better result in terms of impact on the health of consumers when using both the conventional and holistic methods.